Pengaruh Adopsi Kampala Amendments dan Kerangka Yurisdiksi ICC terhadap Efektivitas Penegakan Hukum atas Kejahatan Agresi dalam Sistem Hukum Pidana Internasional - Edo Panangian Simbolon; Dwi Putri Lestariks; Wevy Efticha Sari (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This article examines the influence of the adoption of the Kampala Amendments and the jurisdictional framework of the International Criminal Court (ICC) on the effectiveness of law enforcement against the crime of aggression in the international criminal law system. It outlines the historical background of international criminal tribunals, critiques of previous ad hoc tribunals, and the necessity for a permanent and fair ICC. The primary focus is on the newly defined crime of aggression through the Kampala Amendments and the complex jurisdictional issues involving the authority of the United Nations Security Council. Using a normative juridical approach, this article argues that while the Kampala Amendments have significantly advanced the legal framework, the effective enforcement of jurisdiction over the crime of aggression remains hindered by political and institutional challenges.